Metal-catalyzed C–H bond functionalization of phenol derivatives. Issue 9 (28th February 2020) - Al Mamari, Hamad H.; Štefane, Bogdan; Žugelj, Helena Brodnik
Abstract: Phenols and phenol derivatives constitute important starting materials, synthetic intermediates, and functional moieties of a broad range of chemicals and materials. They represent large production products of benzene and benzene oxidation derivatives and are nowadays progressively available from biomass sources. In the last decades or so, there have been tremendous advances in the field of catalytic C–H bond functionalization, among which metal-catalyzed C–H bond functionalization of phenol derivatives plays a substantial role. In this review, the latest transition metal catalyzed C–H bond functionalizations of phenol derivatives are summarized. The presented methods are powerful tools for various C-H fucntionalziation reactions such as arylation, alkenylation, and acylation as well as annulation of phenol derivatives The presented C-H bond functionalziation of phenol derivatives were carried out in a highly step-economical mannerfrom readily available starting materials. Additionally, this review summarizes the main mechanistic aspects of the covered topic. Graphical abstract: Image 1 Highlights: The review covers advances, and developments in the topic of metal-catalyzed C-H bond functionalization of phenol derivatives with the chelation assistance using directing groups. The review provides information and latest developments of metal-catalyzed C-H bond functionalization of phenol derivatives and mechanistic insights.